Assessment of knowledge and attitude among MAHSA medical students towards HIV/AIDS / Aws Hashim Ali Al-Kadhim ... [et al.] - Ali Al-Kadhim, Aws Hashim; Yousif Al-Ani, Sarah Taha; Alagar, Munandy; Lee, Phon Yong; Devadas, Gomalata; Selvaraj, Chandrasekaran; Azzani, Meram (Faculty of Medicine, 2022)
Introduction: According to the Ministry of Health Statistics, there have been 87,710 confirmed HIV infected cases in Malaysia. The objective of this study is to determine how well MAHSA University medical students knew about HIV/AIDS Methods: This was a cross-sectional questionnaire-based study conducted at MAHSA University's School of Medicine. The surveys focused on different mechanisms of transmission, high-risk behaviours, and prevention strategies. Results A total of 360 medical students participate in this study. Medical students in pre-clinical years had substantially higher knowledge ratings than those in clinical years (p=0.045). Comfortableness dealing with HIV/AIDS patients had the highest stigmatizing score (3.78 ± 0.86). Attitudes toward imposed measures had the lowest stigmatization score (mean 2.60 ± 0.62), knowledge score is significantly correlate with stigmatizing attitude (P=0.004). In addition, higher knowledge scores were shown among medical students who reported to have previous encounters with patients living with HIV/AIDS (PLWHA) (p<0.001). Knowledge scores were significantly low among the patients living with HIV (PEWHIV) (4.2 ± 1.67) (P=0.019). Concerning mother to child transmission of HIV/AIDS infection, clinical medical students showed higher degree of knowledge as compare with preclinical years medical students with P value<0.05. Conclusion: The knowledge of medical students in MAHSA University is generally high, awareness of HIV transmission from mother to child through breast milk is still lacking, indicating that this is the most significant feature that has to be stressed and improved in future medical curriculum for better health care services and public education.